2015
DOI: 10.1165/rcmb.2014-0160oc
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Gene Expression and DNA Methylation during Murine and Human Lung Alveolar Septation

Abstract: DNA methylation, a major epigenetic mechanism, may regulate coordinated expression of multiple genes at specific time points during alveolar septation in lung development. The objective of this study was to identify genes regulated by methylation during normal septation in mice and during disordered septation in bronchopulmonary dysplasia. In mice, newborn lungs (preseptation) and adult lungs (postseptation) were evaluated by microarray analysis of gene expression and immunoprecipitation of methylated DNA foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 48 publications
(50 reference statements)
2
35
0
Order By: Relevance
“…Subsequently, however, genome wide association studies were unable to identify single nucleotide polymorphisms significantly associated with an increased risk of BPD 165, 166 . Additional screens to detect epigenetic marks 167 and changes in long non-coding RNA 168 , have recently been performed, and others such as proteomic and metabolomic screens, have not yet been undertaken. Although these advances in high throughput, ‘omic’ technologies can yield vast amounts of data, heterogeneity in the diseased population and the presence of multiple confounding factors can limit the power to differentiate true signals from background noise.…”
Section: Understanding Bpd Pathobiology – Future Directionsmentioning
confidence: 99%
“…Subsequently, however, genome wide association studies were unable to identify single nucleotide polymorphisms significantly associated with an increased risk of BPD 165, 166 . Additional screens to detect epigenetic marks 167 and changes in long non-coding RNA 168 , have recently been performed, and others such as proteomic and metabolomic screens, have not yet been undertaken. Although these advances in high throughput, ‘omic’ technologies can yield vast amounts of data, heterogeneity in the diseased population and the presence of multiple confounding factors can limit the power to differentiate true signals from background noise.…”
Section: Understanding Bpd Pathobiology – Future Directionsmentioning
confidence: 99%
“…A recent study has shown that 23 genes are differentially methylated with reciprocal changes in expression in patients with BPD compared with preterm or term lungs (Cuna et al , ). Mitoepigenetics such as mitochondrial methylation occur in a variety of cultured mammalian cells, and this process is modulated by DNA methyltransferase 1 in mitochondria (Shock et al , ).…”
Section: Mitochondrial Dysfunction In Chronic Lung Diseasesmentioning
confidence: 99%
“…2 For instance, a recent study identified multiple genes potentially regulated by DNA methylation during normal alveolar septation in the mouse and human lung, and in BPD. 11 In utero smoke exposure modifies the methylation of specific genes, has been associated with changes in indices of global DNA methylation, and biologic pathways impacted through epigenetic changes by in utero smoke are being identified. 12 Maternal prenatal stress, cortisol, in-utero smoke, particulate exposure, and obesity have been shown to be independently associated with child wheeze, likely through programming mechanisms.…”
Section: Prenatal Interventionsmentioning
confidence: 99%